National identity in literature (on «Rule Britannia» by Daphne du Maurier) - Аlsu АshrаpovаZulfiya Zinnatullina,; Popp, Ivan (Opción, 2019)
This article is devoted to the image of the internal other in the novel Rule Britannia by English writer of 20th century Daphne du Maurier via comparative qualitative research methods. As a result, basic stereotypes associated with the English Welsh are described in the novel. Mr. Willis has a typical appearance of Welsh. In conclusion, despite the fact that the Welshman Mr. Willis is seen as an ally in the struggle against an external enemy, the question of its activities in the future and the past remains as an open question.